(untitled) (Current Problems in Rail Vehicles, 2025)
Technical description of the pneumatic train test stand for DAKO braking systems. The description includes the complete pneumatic train stand equipment and its measuring part. The train test stand is used for testing and simulating real conditions of passenger and freight trains up to 1200 m long and containing up to 75 cars for the purpose of developing and verifying the required brake system characteristics. According to EN 15 355, this mainly includes train’s tests of the brake inexhaustibility, the brake release time and verification of the breakthrough speed along the train.